AKTIVITAS ANTIKOLESTEROL DARI KOMBINASI REBUSAN DAUN DAN BUAH SIRSAK (Annona muricata Linn): ANTICHOLESTEROL ACTIVITY OF SOURSOUP LEAF AND FRUIT CONCOCTION COMBINATION (Annona muricata Linn) - Hidayatullah, Hidayatullah; Herawati, Dheasy; Gebo, Yohanes Zaitun Pebi (Faculty of Health Sciences Universitas Maarif Hasyim Latif, 2024)
According to information released by the Indonesian Ministry of Health in 2022, 28% of Indonesia’s population suffered from cholesterol, and the condition claimed the lives of about 7.9% of all individuals worldwide. The use of medication from chemicals can cause side effects on the body, so alternative medicine from natural ingredients is needed, one of which is using a combination of soursop leaves and fruit. In this study, mice were divided into five groups: a negative control group, a positive control group and three treatment groups. The combination therapy given to each treatment group, except a negative control group consisted of boiled soursop leaves and fruit in the following ratios: 1:2, 1:1, and 2:1. The method of determination cholesterol was using immunochromatography test. The study’s findings demonstrated that the group receiving therapy in a ratio of 1:1 and 1:2 was not effective in lowering cholesterol as the group that received boiled soursop leaves and fruit in a ratio of 2:1. A statistical tests emplioyng paired T-tests revealed a significant change (p < 0.05) in cholesterol levels between pre- and post-treatment. This research support the SDGs program, namely good health well-being by utilizing soursop leaves and fruit to reduce cholesterol levels.